Estudo de sistemas híbridos de grafeno com bases nitrogenadas e quercetina - Silva, Julio Cesar da (2021)
In this work we study the graphene for application in the biological area, trying to use it as biological delivery. Flavonoids present biological activities with many health benefits in the prevention of diseases, especially in degenerative functions. However the potential therapeutic application of flavonoids is limited mainly by its poor solubility and bioavailability. To overcome these limitations we propose to load the flavonoid quercetin on a graphene sheet. Our goal is to understand firstly a system composed by graphene-based materials and biological molecules, and then we will investigate the potential properties to use this system as a carrier of biological materials or delivery of drugs in the treatment of diseases as Malaria and Leishmaniasis. We started by performing ab initio calculations based on density functional theory, where we investigate the structural parameters, density of states, band structures, phonon dispersions and absorbance of graphene sheets interacting with quercetin and DNA/RNA nucleobases. The graphene/quercetin hybrid system is an exothermic process with a binding energy of 1.08 eV, without covalent bonding. Our calculated changes on the absorbance in the UV-visible spectra for the graphene/quercetin hybrid system, compared to their bare absorbances, confirm the strong interaction between graphene sheet and quercetin. Although our study has been focusing in the quercetin, the results should be extended to other flavonoids. As graphene is a biocompatible material the drawbacks on the flavonoid administration can be surmounted using graphene as a nanoscale drug delivery system. We seek to investigate this graphene hybrid system for comparison with experimental data obtained through spectroscopic analysis as photoluminescence and Raman.